Classical Islamic Texts Learning Based on Ta'lim as an Instrument for Strengthening Students' Character A Qualitative Study in Islamic Boarding Schools - Wawan elbahri (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
The learning of kitab kuning (classical Islamic texts) in Islamic boarding schools plays an important role in shaping students’ character. The ta’lim approach not only emphasizes the transfer of knowledge but also instills moral values, discipline, and spirituality. This article aims to analyze the strategy of ta’lim-based learning of kitab kuning in shaping students’ character by examining relevant academic sources. The method used is a literature study with content analysis of sources taken from Islamic education journals. The results show that strategies such as bandongan, sorogan, and the habituation of proper conduct significantly influence the development of students’ religious character. In addition, several spelling errors were found in the analyzed sources, indicating the need for improvement in academic writing.